Mobile applications in surgical patient health education: an integrative review - Rafaela Cristina Gomes Machado; Ruth Natalia Teresa Turrini; Cristina Silva Sousa (SciELO, 2020)
Abstract OBJECTIVE To analyze the scientific literature produced on health education through mobile applications for surgical patients. METHOD An integrative literature review performed through consultation in the following portals and/or databases: VHL; PubMed; Web of Science; Scopus; LILACS and CINAHL. The search was guided by the question: "What is the evidence on the use of mobile applications in the health education of surgical patients?" conducted from July to September 2017, including articles published from the year 2000 to 2017. RESULTS Five articles published in international journals in English with varied methodological designs were selected. Among the studies found, 60% used an educational intervention through smartphone applications in the pre and postoperative periods, and 40% of the studies had an evidence level of 2B. CONCLUSION The studies showed that the use of smartphone applications in educating and guiding surgical patients was effective. However, there is still a gap in studies which demonstrate surgical patient education through smartphone applications.